2018
DOI: 10.19087/jveteriner.2017.18.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi dan Faktor Risiko Infeksi Dirofilaria immitis pada Anjing yang Dipotong di Daerah Istimewa Yogyakarta (PREVALENCE AND RISK FACTOR OF THE DIROFILARIA IMMITIS INFECTION IN DOGS SLAUGHTERED IN DAERAH ISTIMEWA YOGYAKARTA)

Abstract: The aim of this study was to determine the prevalence and risk factors Dirofilariaimmitis (D. immitis) infection in dogs slaughtered in Yogyakarta. A total of 151 dogs that were slaughtered from May – November 2013 were examined their heart in order to determine the presence of D. immitis infection. Blood samples were tested using Modified Knott’s Technique for microfilariae examination. The results showed that based on the heart and blood examination the prevalence of D. immitis infection was 14.6 % and 7.9 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
2
0
0
2
Order By: Relevance
“…This finding was similar to some studies conducted in Japan, Turkey, the Dominican Republic, Surinam and Taiwan [37][38][39][40][41]. However, a few studies reported that the infection rate was higher in male dogs due to their stronger attraction to mosquitoes [1,42,43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding was similar to some studies conducted in Japan, Turkey, the Dominican Republic, Surinam and Taiwan [37][38][39][40][41]. However, a few studies reported that the infection rate was higher in male dogs due to their stronger attraction to mosquitoes [1,42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Although there have been studies that showed a link between age and D. immitis infection [43,44], some studies also reported that there was no significant relationship between the age of the dogs with D. immitis infection [45,46]. Likewise, our study supported this finding.…”
Section: Discussionsupporting
confidence: 85%
“…Beberapa penyakit pada anjing di Indonesia sudah pernah dilaporkan pada beberapa sistem organ dan penyakit. Beberapa penelitian yang pernah dilakukan yaitu pada kelainan muskuloskeletal (Purwanto et al, 2015), mata dan telinga, integumen (Kristianti et al, 2016;Timur et al, 2015), infeksi Escherichia coli (Dewandaru et al, 2019), hookworm zoonotik, dirofilariasis (Assady et al, 2019), rabies (Prabandari et al, 2017), protozoa saluran pencernaan (Glantiga et al, 2016), parvovirus (Suartha et al, 2011;Suartini et al, 2019) dan distemper (Erawan et al, 2009).…”
Section: Pendahuluanunclassified
“…The distribution of dirofilarias is very wide and can be found worldwide, including Indonesia, with varying levels of prevalence. The prevalence of dirofilariasis in Indonesia has been reported to vary from 2.2-28.7% in several regions (Satrija et al 2008, Assady et al 2016, Erawan et al 2017, Andiarsa et al 2018. Climate change that has occurred in the last few decades can influence the incidence of diseases, including dirofilariasis.…”
Section: ■ Introductionmentioning
confidence: 99%